La France et le génocide des Tutsis du Rwanda (1994). La version officielle à l’épreuve des archives - Raphaël Doridant; François Graner; Alain Gabet; Sébastien Jahan (Cahiers d’histoire)
The role played by France in the Tutsi genocide in Rwanda in 1994 remains a painful and controversial issue. While the Duclert commission, set up by President Macron, is due to submit its report on this subject next April, the Cahiers d'Histoire questioned two specialists in this problem, François Graner and Raphaël Doridant, members of the association “Survie”, which made a decisive contribution to the understanding of the neocolonial system set up by France, commonly known as "Françafrique". They recently published a book that synthesizes all the knowledge that makes it possible to measure the extent of the involvement of the French authorities in the Tutsi genocide, and bring new revelations from long inaccessible archives.